Exergy analysis of a 1000 MW single reheat supercritical CO2 Brayton cycle coal-fired power plant. (1st October 2018) - Zhou, Jing; Zhang, Chenhao; Su, Sheng; Wang, Yi; Hu, Song; Liu, Liang; Ling, Peng; Zhong, Wenqi; Xiang, Jun
Graphical abstract: Highlights: A comprehensive optimized model for S-CO2 coal-fired power plant is established. Arrangement of S-CO2 coal-fired power plant is compared and optimized. Exergy distributions of a 1000 MW S-CO2 coal-fired power plant are analyzed. The irreversibility of HTR and COL is sensible for S-CO2 coal-fired power plant. Abstract: This study proposes an optimization method for the supercritical carbon dioxide (S-CO2 ) Brayton cycle in a 1000 MW single-reheat S-CO2 coal-fired power plant based on the second law of thermodynamics. The effects of parameters and configurations on S-CO2 cycle efficiencies and component irreversibility are studied. The analysis reveals that variations in parameters and configurations have more remarkable effects on the irreversibility of heat exchangers, particularly on the high-temperature recuperator (HTR) and cooler (COL), than on that of turbo machines. The results show that the optimum parameter of turbines provides a higher expansion ratio for the low-pressure turbine (LPT) than for the high-pressure turbine (HPT). The effects of split ratio to economizer (ECO) have contradicting results on cycle thermal and exergy efficiencies given that the irreversibility of HTR decreases with the increase in the split ratio to ECO. The minimum cycle pressure drastically affects the irreversible interaction between HTR and COL because of the nonlinear characteristics of CO2 near its critical point. Double compression and the Case 2 of the ECO configuration is more reasonable for S-CO2 power plants. The main differences between the S-CO2 and traditional steam power plant are that exergy loss ratio of fuel combustion and exergy efficiency of the water wall, screen heaters, primary heaters are noticeably higher in the S-CO2 boiler than those in the traditional steam boiler. The overall exergy efficiency of the innovative single-reheat 1000 MW S-CO2 coal-fired power plant is 45.4%, which is approximately 3.5% higher than that of the traditional ultra-supercritical steam plant.